2019
DOI: 10.3390/plants8030053
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Transcriptomic and GC-MS Metabolomic Analysis to Characterize Color and Aroma Formation during Tepal Development in Lycoris longituba

Abstract: Lycoris longituba, belonging to the Amaryllidaceae family, is a perennial bulb bearing flowers with diverse colors and fragrance. Selection of cultivars with excellent colored and scented flowers has always been the breeding aim for ornamental plants. However, the molecular mechanisms underlying color fading and aroma production during flower expansion in L. longituba remain unclear. Therefore, to systematically investigate these important biological phenomena, the tepals of L. longituba from different develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 57 publications
0
21
0
1
Order By: Relevance
“…It is proven by many authors that transcription factors are regulating anthocyanin biosynthesis pathway, such as R2R3-MYB, basic helix-loop-helix (bHLH) and WD40repeat (WD40) (Zhao et al 2013;Liu et al 2015). These transcription factors activate or suppress the transcription and expression of target genes by binding to specific DNA sequences and affecting protein-protein interactions, thereby regulating anthocyanin biosynthesis (Yue et al 2019). Many studies have shown that the MYB transcription factors primarily regulate flavonoid pathway genes, while bHLH and WD40 transcription factors play roles in the anthocyanin biosynthesis pathway by binding to MYB transcription factors (Zhao et al 2013;Liu et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is proven by many authors that transcription factors are regulating anthocyanin biosynthesis pathway, such as R2R3-MYB, basic helix-loop-helix (bHLH) and WD40repeat (WD40) (Zhao et al 2013;Liu et al 2015). These transcription factors activate or suppress the transcription and expression of target genes by binding to specific DNA sequences and affecting protein-protein interactions, thereby regulating anthocyanin biosynthesis (Yue et al 2019). Many studies have shown that the MYB transcription factors primarily regulate flavonoid pathway genes, while bHLH and WD40 transcription factors play roles in the anthocyanin biosynthesis pathway by binding to MYB transcription factors (Zhao et al 2013;Liu et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…(Zhang et al 2017), Lycoris longituba Lycoris radiata Herb. (Yue et al 2019) and Silene littorea Silene littorea Brot. (Casimiro-Soriguer et al 2016).…”
Section: Introductionunclassified
“…Flower color is a major characteristic of ornamental value, but the petal color of M. halliana clearly changes from red to pale pink during flower development ( Figure 1A), which affects its ornamental value. This fading of flower color is widespread in Malus plants and other ornamental plants (Jiang et al, 2014;Yue et al, 2019). The phenotype change of flower color of M. halliana presents distinct visible phases, so M. halliana is considered as an excellent model plant for research on flower color.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, 85,622 unigenes were successfully annotated. Recently, a transcriptome report of this specie was published by using 12 tepals samples at different stages as materials, and a large number of unigenes were also obtained (Yue et al, 2019). Although our study only use nine samples, we focused on diverse tissues including leaves, roots, and bulbs at vegetative growth stages.…”
Section: Discussionmentioning
confidence: 99%